2000
DOI: 10.1034/j.1399-3003.2000.16a20.x
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity of human neutrophil peptide-1 against Mycobacterium tuberculosis H37Rv: in vitro and ex vivo study

Abstract: The aim of the study was to investigate the activity of human neutrophil peptide (HNP)-1 to kill Mycobacterium tuberculosis H37Rv in vitro and ex vivo in the murine macrophage cell line J744A.1 on the basis of colony forming units. Macromolecular biosynthesis was studied by monitoring the incorporation of radioactive precursors into different macromolecules. The binding and localization studies were carried out with radioiodinated HNP-1 whereas the cytotoxicity of HNP-1 to macrophages was determined by trypan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
61
1
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(69 citation statements)
references
References 14 publications
5
61
1
2
Order By: Relevance
“…These data are consistent with reports from Peschel et al, indicating that M. tuberculosis contains a gene or genes related to the MprF gene of Staphylococcus aureus, which mediates resistance to HNP in that species (28). Two groups have reported that HNP-1 can kill M. tuberculosis in vitro (24,32). While we have used HNP from the same sources against the same strains of M. tuberculosis growing in the same medium as these groups, we have not observed mycobactericidal activity of HNP.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…These data are consistent with reports from Peschel et al, indicating that M. tuberculosis contains a gene or genes related to the MprF gene of Staphylococcus aureus, which mediates resistance to HNP in that species (28). Two groups have reported that HNP-1 can kill M. tuberculosis in vitro (24,32). While we have used HNP from the same sources against the same strains of M. tuberculosis growing in the same medium as these groups, we have not observed mycobactericidal activity of HNP.…”
Section: Discussionsupporting
confidence: 82%
“…If the amount of HNP bound to M. tuberculosis varies with the amount of HNP in the medium, it should be possible to construct a standard curve relating the exposure to HNP to the amount of specific antibody staining. The MIC sufficient to prevent growth of M. tuberculosis has previously been reported to be 2.0 to 2.5 g/ml (32,33). Therefore, we incubated M. tuberculosis (Erdman strain) with HNP-1 at concentrations from 0.1 to 33 g/ml for 24 h at 37°C, after which the tubercle bacilli were quickly washed and fixed in formalin.…”
Section: Fig 3 Lack Of Effect Of Roi or Rni Inhibitors On Killing Bmentioning
confidence: 99%
“…Among the proteins known to exhibit bactericidal activity against mycobacteria, EPO seems to be the most potent. The other known mycobactericidal proteins, such as defensins (38,43,44), protregrins (35), NK lysins (2), and granulysin (19,48), exhibit significant mycobactericidal activity starting at a concentration of 10 M. After 4 to 5 h, a minimal effect was found, and at least 24 h was required before significant activity of these proteins was observed. Additionally, glutathione and S-nitrosoglutathione are able to kill mycobacteria, but in this case the activity is even weaker, on a molar basis, than the activities of the proteins mentioned above.…”
Section: Discussionmentioning
confidence: 99%
“…Other possible substrates of the MmpL proteins are the antimicrobial peptides produced by the host. Antimycobacterial activity has been found in several defensins, such as human and rabbit neutrophil peptide-1 or porcine protegrin (25,44,45). The MtrD protein of Neisseria gonorrhoeae, which is also a member of the RND family, modulates susceptibility to antibacterial peptides (43).…”
Section: Discussionmentioning
confidence: 99%